The influence of laser parameters and scanning strategies on the mechanical properties of a stochastic porous material. (5th October 2017) - Ghouse, Shaaz; Babu, Sarat; Van Arkel, Richard J.; Nai, Kenneth; Hooper, Paul A.; Jeffers, Jonathan R.T.
Abstract: Additive manufacturing enables architectured porous material design, but 3D-CAD modelling of these materials is prohibitively computationally expensive. This bottleneck can be removed using a line-based representation of porous materials instead, with strut thickness controlled by the supplied laser energy. This study investigated how laser energy and scan strategy affects strut thickness and mechanical strength of porous materials. Specimens were manufactured using varying laser parameters, 3 scan strategies (Contour, Points, Pulsing), 2 porous architectures and 2 materials (Titanium, Stainless Steel), with strut thickness, density, modulus, mechanical strength and build time measured. Struts could be built successfully as low as 15° with a minimum diameter of 0.13 mm. Strut thickness was linearly related to the specific enthalpy delivered by the laser to the melt-pool. For a given stiffness, Titanium specimens built at low power/slow speed had a 10% higher strength than those built at high power/fast speed. The opposite was found in Stainless Steel. As specimen stiffness increased, the Contour Strategy produced samples with the highest strength:stiffness and strength:weight ratio. The Points strategy offered the fastest build time, 20% and 100% faster than the Contour and Pulsing strategies, respectively. This work highlights the importance of optimising build parameters to maximize mechanical performance. Graphical abstract: Highlights: Stochastic architectured porous materials were additively manufactured in Titanium and Stainless Steel The effect of laser parameters and scan strategies on strut thickness and strength of porous materials were investigated A linear relationship was found between the specific enthalpy, delivered by the laser to the meltpool, and strut thickness The optimum rate of energy for maximising strength of a porous material for a given stiffness was material dependent Maximizing the strength:stiffness and strength:weight ratio of a porous material is dependent on the scan strategy used